Movement-induced uncoupling of primary sensory and motor areas in focal task-specific hand dystonia - Melgari, J.M.; Zappasodi, F.; Porcaro, C.; Tomasevic, L.; Cassetta, E.; Rossini, P.M.; Tecchio, F. (Neuroscience, 2013)
•Through an ad hoc procedure (FSS), distinct sources were identified in S1 and M1.•No differences were found between spectral properties of patients and controls for either S1 and M1.•Gamma band S1–M1 coherence was bilaterally reduced in patients during movement.•In focal hand dystonia, uncoupling replaces the physiological sensorimotor coupling.•Bi-hemispheric abnormalities in unilateral dystonia suggest endophenotypic traits. Due to growing evidence of sensorimotor integration impairment in focal task-specific hand dystonia, we aimed at describing primary sensory (S1) and primary motor (M1) cortex source activities and their functional cross-talk during a non-dystonia-inducing sensorimotor task free of biases generated by the interfering with the occurrence of dystonic movements. Magnetoencephalographic brain signals and opponens pollicis (OP) electromyographic activities were acquired at rest and during a simple isometric contraction performed either alone or in combination with median nerve stimulation. The task was performed separately with the right and left hand by eight patients suffering from focal task-specific hand dystonia and by eight healthy volunteers. Through an ad hoc procedure Functional Source Separation (FSS), distinct sources were identified in S1 (FSS1) and M1 (FSM1) devoted to hand control. Spectral properties and functional coupling (coherence) between the two sources were assessed in alpha [8,13]Hz, beta [14,32]Hz and gamma [33,45]Hz frequency bands. No differences were found between spectral properties of patients and controls for either FSM1 or FSS1 cerebral sources. Functional coupling between FSM1 and FSS1 (gamma band coherence), while comparable between dystonic patients and healthy controls at rest, was selectively reduced in patients during movement. All findings were present in both hemispheres. Because previous literature has shown that gamma-band sensory–motor synchronization reflects an efficiency index of sensory–motor integration, our data demonstrate that, in dystonic patients, uncoupling replaces the functional coupling required for efficient sensory–motor control during motor exertion. The presence of bi-hemispheric abnormalities in unilateral hand dystonia supports the presence of an endophenotypic trait.